The Use of Air Pressure Measurements Within a Sealed Moonpool for Sea-State Estimation - Brendan Walsh; Robert Carolan; Mark Boland; Thomas Dooley; Thomas Kelly (Journal of Marine Science and Engineering)
To assess the viability of locations for wave energy farms and design effective coastal protection measures, knowledge of local wave regimes is required. The work described herein aims to develop a low-cost, self-powering wave-measuring device that comprises a floating buoy with a central moonpool. The relative motion of the water level in the moonpool to the buoy will pressurise and depressurise the air above the water column. The variation in air pressure may then be used to estimate the sea-state incident upon the buoy. Small-scale proof of concept tank testing was conducted at a 1:20 scale and at a larger 1:2.4 scale before a full-scale prototype was deployed at the Smartbay test site facility in Galway Bay, Ireland. A number of techniques by which full-scale sea states may be estimated from the pressure spectrum are explored. A successful technique, based on the average of multiple linear squared magnitude of the transfer functions obtained under different wave regimes is developed. The applicability of this technique is then confirmed using validation data obtained during the full-scale sea trials. While the technique has proven useful, investigation into potential seasonal bias has been conducted, and suggestions for further improvements to the technique, based on further calibration testing in real sea states, are proposed.